Некомпенсированные вюрмские вымирания. Сообщение 5. Кризис в Палеарктике - Пучков, П.В. (Вестник зоологии, 1993)
Predation by man is the principal cause of the extinction of mammoth, forest and namadic elephants, all Palaear-ctic rhinos. With the depression of these giants peculiar plant communities, sustained by their activity (mosaic woodlands, parklands and cryopnytic savannah associations), were supplanted, according to each climatic zone, by tundras, taiga or dense leaf-be aring forests. Ungulates and carnivores could not use «mammoths’ paths» through thickets and snow any more. In steppes (both on plains and on highlands) vegetation became less mosaic, and fires more frequent and intensive (in absense of gigantic grazers more grass than before rested uneaten and dried up). Because of all this, territories, fit for viable populations of such herbivores as Ursus spelaeus, U. rossicus, Me-gaceros spp., Spirocerus kiakhtensis, Parabubalis capricornis, Ovibos moschatus, Bos grunniens baikalensis, Siberian race of Bos (Bison) priscus, Equus hidruntinus, forest races of E. caballus s. 1. drastically shrinked. Diminishing populations of these species became more and more isolated and were gradually outsted by multiplying populations of extant herbivores more fit for existence in the environment without pachyderms. So successful competitors of Bos priscus in Siberia were extant Cervidae, in steppic zone it was Bos primigenius. Subsidiary factors of extinction of the mentioned herbivores were changes of the competitive conditions caused by human hunting and burning activity. The predation from packs of wolves that multiplied because of the decline of their foes (lions, leopards, cave hyenas) could also accelerate the decline of poulations of herbivores, depressed by afore-mentioned environmental changes. It may be the main reason of extinction of european tahr (Hemitrogus bonali). The principal cause of the decline of cave lions, cave hyenas, leopards and dholes in Northern Eurasia was the impoverishment of large prey. Besides this the 3 first species unsuccessfully comleted with man, and dhole — with wolf, previously suppressed by larger predators. The extinction of a series of soil mites belonging to Oribatidae is linked with the change of soil conditions after the cessation of grazing activity of mammoths and other extinct herbivores. Extinction of Palaearctic pachyderms was long-lasing and gradual. Therefore considerably more forms than in America could adapt themselves to environmental changes. This is the main reason of the conservation of horses in Palaearctic and their expiration in America. Climatic factors played only subsidiary role in Wurm extinctions by accelerating or retarding the process.